Behaviour and modelling of connections in cold-formed steel single C-section portal frames. (October 2019) - Rinchen,; Rasmussen, Kim J.R.
Abstract: The flexural behaviour of eaves, apex and base connections for cold-formed steel single C-section portal frames is investigated through a series of connection tests and analyses of corresponding finite element models. The moment-rotation characteristics of the eaves, apex and base connections from the respective connection tests and the numerical models indicate good agreement between. The attainment of ultimate load by the eaves and the apex connection was normally preceded by significant deformation of connecting brackets. The eaves connections reached its ultimate load capacities upon fracture of screws or ply bearing of M8 bolts on the C-section lips while the apex connections attained their ultimate load capacities with the formation of inelastic buckling near the compression flange-web junction of one of the adjoining beams. The base connection tests exhibited large rotational deformation and capacity to deform with inelasticity mostly concentrated in the connector bracket. Based on the tests and numerical analyses, simplified nonlinear moment-rotation relations are established for eaves, apex and base connections. Highlights: The behaviour of the main connections in cold-formed steel single C-section portal frames is investigated. Semi-rigid moment-rotation characteristics of eaves, apex and base connections are derived. Advanced numerical modelling of frame connections using shell elements is presented.